RHIZOBIUM JAPONICUM BACTERY INCLUDES SOME FOSSOR PLANT FOSSTIM3 HAS BEEN USED TO BATTERIAL BIOTERIES - Mannopova, M.; Hamdamov, J.U.; Berdaliev, H.N. (International Journal of Psychosocial Rehabilitation, 2020)
Infection of these bacteria in the fields where soybeans were first planted using FOSSTIM3 bacterial biofertilizer, which contains Rhizobium japonicum bacteria and phosphorus decomposer, to form endogenous bacteria in the root of the soybean plant